Rationale and design of the Drug‐Eluting Stents vs Bare‐Metal Stents in Saphenous Vein Graft Angioplasty (DIVA) Trial. Issue 11 (25th August 2017) - Brilakis, Emmanouil S.; Banerjee, Subhash; Edson, Robert; Shunk, Kendrick; Goldman, Steven; Holmes, David R.; Bhatt, Deepak L.; Rao, Sunil V.; Smith, Mark W.; Sather, Mike; Colling, Cindy; Kar, Biswajit; et al.
Abstract : VA Cooperative Studies Program #571 (DIVA) was designed to evaluate the efficacy of drug‐eluting stents (DES) for reducing aortocoronary saphenous vein bypass graft (SVG) failure when compared with bare‐metal stents (BMS) in participants undergoing stenting of de novo SVG lesions. Participants undergoing clinically indicated stenting of de novo SVG lesions were randomized in a 1:1 ratio to DES or BMS. Randomization was stratified by presence/absence of diabetes mellitus and the number of target SVG lesions (1 vs ≥2) within each participating site. At sites that did not routinely administer 12‐months of dual antiplatelet therapy after SVG stenting participants without acute coronary syndromes received 1 month of open‐label clopidogrel, followed by 11 months of clopidogrel for those assigned to DES and 11 months of placebo for those assigned to BMS. The primary endpoint was the 12‐month incidence of target‐vessel failure (defined as the composite of cardiac death, target‐vessel myocardial infarction, or target‐vessel revascularization). Secondary endpoints included the incidence of other clinical endpoints and the incremental cost‐effectiveness of DES relative to BMS. Due to lower‐than‐anticipated target‐vessel failure rates, target enrollment was increased from 519 to 762. The study had randomized 599 participants when recruitment ended in December 2015. The DIVA trial will provide clarity on the appropriate stent type for de novo SVG lesions.